PERIlAKU PEOAGANG TENTANG FASILITAS SANITASI 01 PASAR SAYUR MAGETAN TAHUN 2014 - Sari Lisa Sugiarti; Prijono Sigit; Moch Yulianto (Poltekkes Kemenkes Surabaya, 2014)
Magetan vegetable market is a class 1 market in accordancewith Regulation Number 3 2011. It isthe largest market in kabupaten Magetan, as seen from the large area coverage and number of tradersdoing business and amount of retribution collected everyday. Magetan vegetable market is located JalanMayjen Sungkono Number 07 Magetan covering an area of 10,000 m2 and devided into 5 blocks. Thedaily operating hours is 04.00 pm - 21.00 pm.The sanitation facilities especially the bathrooms or toilets and garbage bins in this market are inpoor condition, while sellers operating in this market seemed not to care about the state of the sanitationfacilities. The purpose of this study was to illustrate the behavioral aspects of traders with regard tosanitation facilities in Magetan Vegetable Market, by assessingtheir working knowledge, attitude, actionsand behavior of traders toward the care of sanitation facilities provided in the market.This was a descriptive, a cross-sectional study that performed directly in the field. The studycovered a total of 295 respondents drawn from a total population of 1,121 merchants by quota type non-probability sampling.With regard to the level of merchants' behavior in the Market, their behaviour relating to themaintenance of sanitation facilities was poor. The level of good behavior was represented by 40,67%, andpoor behaviour was indicated by 54,33% of respondents. Their working knowledge associated with effortsthe maintenance sanitation facilities in this Vegetable Market can be divided into